Lysine and Energy Trends in Feeding Modern Commercial Broilers - Cerrate , S.; Corzo, A. (International Journal of Poultry Science, 2018)
Background and Objective: It seems that current broiler chickens have modified the dietary nutrient needs and body composition over time. Further, the relationships between dietary nutrients and feed cost or biological nutrient requirements are unknown. The aim of this study was to understand and explain current energy and amino acid tendencies of dietary levels and requirements, to evaluate relationships between dietary energy and lysine among levels, feed cost and requirements and to compare energy and lysine efficiency from 2001-2017. Methodology: Data from literature were evaluated to predict the dietary ME and amino acids as well as the body fat content by multiple regression. Actual dietary ME and digestible lysine levels were linearly regressed with diet cost and ME and lysine requirements. Efficiencies of lysine and ME were calculated taking into account the broiler genetic improvement through body composition. Results: Dietary energy levels have been reduced at a rate of 5 kcal per year while digestible lysine has increased by 0.009% per year from 2001-2017. Nutritionists during the process of selecting dietary energy and lysine levels have been influenced by feed cost (r2 = 0.75) and lysine requirements (r2 = 0.86), respectively. During a period of 16 years, modern broiler chickens deposit less body fat (-6% of body weight) and more body protein (+4% of body weight) and convert energy and amino acids into meat more efficiently than older broiler genotypes. Conclusion: These data indicate that dietary energy and lysine are reduced and increased, respectively, influenced by feed cost and requirements, resulting in better energy and lysine efficiencies due to feed intake and body composition changes.